Towards a Latin American Policy: A liberating and intercultural proposal (Colloquia, Academic Journal of Culture and Thought, 2022)
The concept of Politics has undergone a significant process of narrowing, reaching contemporary times as a concept that seeks to define the whole by an inarticulate and insufficient part. Therefore, the aim of this article is to reflect on politics from Latin American materiality and with a liberating and intercultural ethic. This reflection locates and articulates two of the most significant philosophical currents in Latin America, Liberation and Intercultural. Additionally, it positions itself in a critical dialogue with the orthodox ways of approaching politics and politics.